How can we retain them? An investigation into the early cancellation of courses in a distance learning institution - van Schoor, WA; Potgieter , D (South African Journal of Higher Education, 2011)
Throughput and retention are important issues in higher education in South Africa mainly due to the stronger emphasis on accountability from funding agencies like the Department of Education. This study, which is set in a distance education institution, was aimed at understanding why students cancel courses early on in the academic year. A telephone survey was conducted with a sample of 333 subjects. The data indicate that 19 per cent of the sample attributed the reasons for cancellation to changes in their work or living conditions. Personal and financial problems were responsible for 17 per cent of the variation while 11 per cent gave reasons that were directly attributable to institutional processes. Incorrect course selection contributed 13 per cent of the cancellations while 23 per cent of the students could not cope with the academic demands. The data are discussed against the framework of a Managed Open Admission Project designed to deal with the identified issues.